Customers’ acceptance intention of self-service technology in casual dining restaurant: Expanding UTAUT with perceived risk and perceived vulnerability - Shela Muktamarisa; Adi Zakaria Afiff (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The COVID-19 pandemic has forced restaurants to adopt contactless self-service technology to address customers' level of vulnerability to COVID-19. This study examines important behavioral and user acceptance of self-service technology (SST) variables based on the Unified Theory of Use and Acceptance of Technology (UTAUT) model and enhanced to incorporate perceived risk and moderating effects of perceived vulnerability to COVID-19. The casual dining restaurants were chosen as the context of the study as this industry usually relies more on personal services than on SST, so the impact of environmental change can be seen more clearly. A questionnaire survey was created to gather empirical data about the usage of self-service technology through online data collection, and a quantitative method was adopted for data analysis. A structural analysis was conducted with the Partial Least Squares method to test the hypothetical relationship between the constructs proposed in the conceptual model. The contribution of this study is to analyze the use of technology in casual restaurant service settings in the context of the COVID-19 pandemic to provide an understanding of SST usage and practical implications for service development in the casual restaurants industry.